Perancangan UI/UX Pada Aplikasi Serikat Pekerja Kereta Api Dengan Metode Design Thinking - Bahrudin; Irfan Mahendra (LPPM Universitas Putera Batam, 2025)
The SPKA application is a mobile device that can help users in associating using the application. Based on the results of observations and interviews, the use of the SPKA application is still not optimal and lacks attention to user interface (UI) and user experience (UX) design, causing inconvenience for users when using the application. The goal of the testing is to update the UI/UX of the SPKA application by applying the design thinking method. The choice was made for the design thinking approach because it emphasizes creativity in creating new solutions and places a strong emphasis on understanding user needs. This study includes data collection and analysis involving five stages of the design thinking method, namely empathize, define, ideate, prototype, and testing. The application of the design thinking method in the development of UI/UX interfaces produces results that can achieve the goals of the method to enhance user satisfaction and utility. Support depends on the results of testing with the System Usability Scale method for the SPKA application, which achieved a final score of 85 and received a B classification on the assessment scale. Thus, this indicates that users appreciate the high level of usability of the SPKA application. The UI/UX design of the SPKA application is expected to serve as a model for the development of SPKA applications in the future.